Pengaruh Keefektifan Pengendalian Internal, Persepsi Kesesuaian Kompensasi, Dan Moralitas Individu Terhadap Kecenderungan Kecurangan Akuntansi - Anastasia Anastasia; Sparta Sparta (Universitas Multimedia Nusantara, 2014)
Case of accounting fraud has increased in many countries and organization. It brings a loss to firms and investors. This study aims to analyze the effect of Internal Control Effectiveness, Perception of Suitability of Compensation, and Individual Morality towards Accounting Fraud Tendencies. This study used quantitative method. Questionnaires used for collecting the data from Finance and Accounting Staff working at Private Companies in Tangerang and Jakarta. Total sampel used for this study are 109 sampel. The examination of hypothesis method using multivariate regretion. Result of this study indicates that internal control effectiveness and perception of suitability of compensation doesn’t have significant effect towards accounting fraud tendency. Individual morality significantly affect the occurance of accounting fraud tendency. Key Words: Accounting Fraud Tendencies, Individual Morality, Internal Control Effectiveness, Perception of Suitability of Compensation.